2016
DOI: 10.1257/pol.20120393
|View full text |Cite
|
Sign up to set email alerts
|

Capacity and Utilization in Health Care: The Effect of Empty Beds on Neonatal Intensive Care Admission

Abstract: Because geographic variation in medical care utilization is jointly determined by both supply and demand, it is difficult to empirically estimate whether capacity itself has a causal impact on utilization in health care. In this paper, I exploit short-term variation in Neonatal Intensive Care Unit (NICU) capacity that is unlikely to be correlated with unobserved demand determinants. I find that available NICU beds have little to no effect on NICU utilization for the sickest infants, but do increase utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…We found that babies born at hospitals with more NICU beds were more likely to have NICU admissions, which is Table 2 Proportion of births with a given condition that were admitted to a neonatal intensive care unit, overall sample, and variation across hospitals. consistent with prior studies [24,25]. Examination of different hospital processes may allow for creation of standardized protocols or system processes to help reduce unnecessary NICU admissions, and thereby decrease adverse financial, psychosocial, and downstream health effects.…”
Section: Discussionsupporting
confidence: 60%
“…We found that babies born at hospitals with more NICU beds were more likely to have NICU admissions, which is Table 2 Proportion of births with a given condition that were admitted to a neonatal intensive care unit, overall sample, and variation across hospitals. consistent with prior studies [24,25]. Examination of different hospital processes may allow for creation of standardized protocols or system processes to help reduce unnecessary NICU admissions, and thereby decrease adverse financial, psychosocial, and downstream health effects.…”
Section: Discussionsupporting
confidence: 60%
“…Infants are admitted for many nonacute reasons, such as hypoglycemia and rule-out sepsis, and for specific interventions such as antibiotic administration or line placement. 23 More practically, bed supply 24,25 and supply-sensitive care 26 -28 may play roles in admission rates. In recent research, authors have pointed to possible overuse of NICU care, particularly among larger infants.…”
Section: Discussionmentioning
confidence: 99%
“…16 Similarly, newborn intensive care unit bed supply was associated with increased admission rates for newborns with good health status. 17,18 These findings extend into primary care where outpatient visits increase with increased physician supply even after accounting for sociodemographic differences. 19 This may be extended to our finding that ED high utilizers from 1 geographical location in our com- munity increased at the same time that more resources became available.…”
Section: Discussionmentioning
confidence: 71%